Isolation of nanobodies with potential to reduce patients' IgE binding to Bet v 1. Issue 6 (16th December 2021) - Zettl, Ines; Ivanova, Tatiana; Strobl, Maria R.; Weichwald, Christina; Goryainova, Oksana; Khan, Evgenia; Rutovskaya, Marina V.; Focke‐Tejkl, Margarete; Drescher, Anja; Bohle, Barbara; Flicker, Sabine; Tillib, Sergei V.
Abstract: Background: Recent studies showed that a single injection of human monoclonal allergen‐specific IgG antibodies significantly reduced allergic symptoms in birch pollen‐allergic patients. Since the production of full monoclonal antibodies in sufficient amounts is laborious and expensive, we sought to investigate if smaller recombinant allergen‐specific antibody fragments, that is, nanobodies, have similar protective potential. For this purpose, nanobodies specific for Bet v 1, the major birch pollen allergen, were generated to evaluate their efficacy to inhibit IgE‐mediated responses. Methods: A cDNA‐VHH library was constructed from a camel immunized with Bet v 1 and screened for Bet v 1 binders encoding sequences by phage display. Selected nanobodies were expressed, purified, and analyzed in regards of epitope‐specificity and affinity to Bet v 1. Furthermore, cross‐reactivity to Bet v 1‐homologues from alder, hazel and apple, and their usefulness to inhibit IgE binding and allergen‐induced basophil activation were investigated. Results: We isolated three nanobodies that recognize Bet v 1 with high affinity and cross‐react with Aln g 1 (alder) and Cor a 1 (hazel). Their epitopes were mapped to the alpha‐helix at the C‐terminus of Bet v 1. All nanobodies inhibited allergic patients' polyclonal IgE binding to Bet v 1, Aln g 1, and Cor a 1 and partially suppressed Bet v 1‐induced basophil activation. Conclusion: We identified high‐affinity Bet v 1‐specific nanobodies that recognize an important IgE epitope and reduce allergen‐induced basophil activation revealing the first proof that allergen‐specific nanobodies are useful tools for future treatment of pollen allergy. Abstract : For the first time, Bet v 1‐specific nanobody encoding sequences from an immunized camel were isolated. Generated nanobodies bind Bet v 1 with high affinity and cross‐react with Bet v 1 homologous allergens from alder and hazel. Nanobodies reduce polyclonal IgE binding to Bet v 1 and cross‐reactive allergens, and partially decrease Bet v 1‐induced IgE‐mediated basophil activation.Abbreviation: Nbs, nanobodies; VHH, variable domain of a heavy‐chain antibody